Water Level Sensing in a Steel Vessel Using A0 and Quasi-Scholte Waves. (20th December 2017) - Guo, Peng; Deng, Bo; Lan, Xiang; Zhang, Kaili; Li, Hongyuan; Tian, Zhenhua; Xu, Hong
Abstract : This paper presents a water level sensing method using guided waves of A0 and quasi-Scholte modes. Theoretical, numerical, and experimental studies are performed to investigate the properties of both the A0 and quasi-Scholte modes. The comparative study of dispersion curves reveals that the plate with one side in water supports a quasi-Scholte mode besides Lamb modes. In addition, group velocities of A0 and quasi-Scholte modes are different. It is also found that the low-frequency A0 mode propagating in a free plate can convert to the quasi-Scholte mode when the plate has one side in water. Based on the velocity difference and mode conversion, a water level sensing method is developed. For the proof of concept, a laboratory experiment using a pitch-catch configuration with two piezoelectric transducers is designed for sensing water level in a steel vessel. The experimental results show that the travelling time between the two transducers linearly increases with the increase of water level and agree well with the theoretical predictions.